Treatment of tenun dye wastewater using membrane bioreactor (MBR) - Radhiatul Asma, Abdul Rashid (2014)
The Textile Industry makes a big contribution to the economic growth due to high demands locally and from abroad. But, textile industry is one of the most chemically intensive industries on the earth and the major polluter of portable water. Wastewater from dyeing in textile plant is often rich in colour, containing residual of dyes and chemical. This wastewater needs proper treatment before releasing into the environment. The purpose of study is to determine the characteristic of treated tenun dye wastewater and effect of Hydraulic Retention Time (HRT) of 24hours, 48 hours and 72 hours. Membrane Bioreactor (MBR) is used to treat tenun dye wastewater with addition activated sludge to assist biodegradation of tenun dye wastewater. Membrane bioreactor is process combination of activated sludge treatment and membrane filtration. Activated sludge is an active biological material produced by activated sludge plants, especially in aerobic, anaerobic and aeration system. The parameters that have observed were COD, BOD, TSS, Colour and MISS. The results show that the COD value is decrease on 48 hour and increase in 72 hour. While BOD results show that from initial value, the value for 24 hour is decrease and then the value increase in 72 hour. The value of BOD supposed to decrease with increasing time. The TSS value is decrease since the particle cannot pass through the filter as the particle blocked in time during filtration. Then the MLSS is increase due to growth of microorganism. The high percentage color removal is 24%. It is show that MBR has potential to remove the particles that available in tenun dye wastewater. The data collected is used to improve the effectiveness of the research of dye treatment using MBR.